Enhanced continuous biohydrogen production using dynamic membrane with conductive biofilm supporter. (June 2023) - Yang, Jisu; Sim, Young-Bo; Moon Kim, Saint; Joo, Hwan-Hong; Jung, Ju-Hyeong; Kim, Sang-Hyoun
Graphical abstract: Highlights: A conductive biofilm supporter increased continuous H2 production by 16.8%. The elevated H2 production was accompanied with higher NADH/NAD + and lowered ORP. Metabolic flux shifted from NADH-consuming pathways to H2 -producing acetogenesis. Dominant H2 producers were affiliated with electroactive Clostridium sp. Abstract: The present study investigated the effect of a conductive biofilm supporter on continuous production of biohydrogen in a dynamic membrane bioreactor (DMBR). Two lab-scale DMBRs were operated: one with a nonconductive polyester mesh (DMBR I) and the other with a conductive stainless-steel mesh (DMBR II). The highest average hydrogen productivity and the yield were 16.8% greater in DMBR II than in DMBR I, with values of 51.64 ± 0.66 L/L-d and 2.01 ± 0.03 mol H2 /mol hexoseconsumed, respectively. The improved hydrogen production was concurrent with a higher NADH/NAD + ratio and a lower ORP (Oxidation-reduction potential). Metabolic flux analysis implied that the conductive supporter promoted H2 -producing acetogenesis and repressed competitive NADH-consuming pathways, such as homoacetogenesis and lactate production. Microbial community analysis revealed that electroactive Clostridium sp. were the dominant H2 producers in DMBR II. Conclusively, conductive meshes may be useful as biofilm supporters of dynamic membranes during H2 production for selectively enhancing H2 -producing pathways.